Prevalence, clinical profiles, and outcome of hypertension in renal transplant recipients - A T Maasila; C Subash Chandrabose; T Balasubramaniyan; N Gopalakrishnanan; J Dhanapriya; T Dineshkumar; R Sakthirajan; S Ganesh Aravind (Indian Journal of Transplantation, 2018)
Background: Hypertension is more prevalent risk factor for cardiovascular morbidity and mortality among renal transplant recipients. Materials and Methods: It is a retrospective study conducted to assess the prevalence, clinical profiles, and outcome of hypertension in renal transplant recipients. Posttransplant hypertension was defined as systolic blood pressure (BP) ≥140 mmHg, diastolic BP ≥80 mmHg, or the need of antihypertensive medication. Donor and recipient demographical details were obtained from medical records. Patients who underwent second renal transplant or graft nephrectomy were excluded from the study. Results: Among 375 patients, 88% were male. The mean age of our study population was 35.82 ± 9.37 years. Almost 82.67% of patients had posttransplant hypertension, of which 80.97% had pretransplant hypertension. Nearly 19.03% patients developed hypertension posttransplant. Following transplantation, hypertension resolved in 12.85%. The prevalence of well controlled, poorly controlled, and resistant posttransplant hypertension was 49.68%, 50.32%, and 7.42%, respectively. Majority of them (90.97%) received calcium channel blockers. In univariate analyses, recipient sex, pretransplant hypertension, etiology of kidney disease, female donors, female donors of male recipient's subgroup, use of cyclosporine, left ventricular mass, weight gain, and presence of metabolic syndrome were statistically significant. In multiple logistic regression analyses, recipient sex, presence of metabolic syndrome, and use of cyclosporine were associated with posttransplant hypertension. Kaplan–Meier analyses showed low graft survival in posttransplant hypertensive patients when compared to normotensives. Conclusion: The prevalence of hypertension in our renal transplant recipients was 82.67%. Early identification of risk factors, treatment, and adequate BP control will improve the long-term patient, graft survival.